Short-term effects of air pollution on mortality in the Klang valley, Malaysia / Wan Rozita Wan Mahiyuddin - Wan Mahiyuddin, Wan Rozita (Institute of Graduate Studies, UiTM, 2012)
The problem of urban air pollution is felt worldwide and transcends national boundaries. Malaysia’s goal to be a fully industrialized country by 2020 has started impacting on the quality of air in major cities. The main objective of this study is to estimate the mortality risk attributed to air pollution in Klang Valley, Malaysia, based on a sevenyear daily data from 2000 to 2006. The mortality data were provided by the Statistics Department. The daily level of five main pollutants, namely, particulate matter less than 10 g/m3 (PM10), nitrogen dioxide (NO2), sulfur dioxide (SO2), ozone (O3) and carbon monoxide (CO ) were obtained from the Department of Environment, while relevant meteorological information was obtained from the Meteorological Services Department.